PENGARUH SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI, SISTEM INFORMASI PADA KESIAPAN PENERAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH BERBASIS AKRUAL - Bayu Permana, Ida Bagus Gede; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
Based on Government Regulation No. 71 Year 2010, which was confirmed by the Minister of Home Affairs number 63 in 2013, that the provincial government, district and city already must implement accrual-based financial statements in the financial statements of 2015. Therefore, the readiness of the implementation of the new system requires support of the readiness of Human Resources, Organizational commitment and Systems. This study aimed to examine the effect of Human Resources, Organizational Commitment and Implementation Readiness Information System on Local Government Finance Report Based Accrual. Research was conducted on the financial section Secretariat Badung regency. This study uses data analysis techniques Regression using 74 respondents. Hypothesis test results indicate that the influence of Human Resources, Organizational Commitment, and Information Systems Readiness significant positive effect on the adoption of Local Government Finance Report Based Accrual.
Keywords: the quality of human resources, organizational commitment, information systems, implementation of accrual-based SAP